Modulation of host cell apoptotic pathways by intracellular pathogens - Friedrich, Anja; Pechstein, Julian; Berens, Christian; Lührmann, Anja (Current Opinion in Microbiology, 2017)
Nearly all steps of the host cell apoptotic cascade can be subverted by intracellular microorganisms. Some pathogens modulate early steps and interfere with sensing of extracellular signals, cellular stress or signal transduction; others target Bcl-2 proteins, caspases, or inhibitor of apoptosis proteins (IAPs). In many cases the exact molecular mechanisms leading to interference with the host cell apoptotic cascade are still unknown. However, there are some examples where bacterial factors that modulate host cell death have been identified. In this review we will summarize recent findings on how intracellular pathogens or their secreted proteins alter the intrinsic and/or extrinsic host cell apoptotic pathways.
EVALuna2:7732

The Coxiella burnetii effector protein CaeB modulates endoplasmatic reticulum (ER) stress signalling and is required for efficient replication in Galleria mellonella - Friedrich, Anja; Beare, Paul A.; Schulze-Luehrmann, Jan; Cordsmeier, Arne; Pazen, Tobias; Sonnewald, Sophia; Lührmann, Anja (Cellular Microbiology, 2021)
The obligate intracellular pathogen Coxiella burnetii is the causative agent of the zoonosis Q fever. C. burnetii infection can have severe outcomes due to the development of chronic infection. To establish and maintain an infection, C. burnetii depends on a functional type IVB secretion system (T4BSS) and, thus, on the translocation of effector proteins into the host cell. Here, we showed that the C. burnetii T4BSS effector protein CaeB targets the conserved endoplasmatic reticulum (ER) stress sensor IRE1 during ER stress in mammalian and plant cells. CaeB-induced upregulation of IRE1 RNase activity was essential for CaeB-mediated inhibition of ER stress-induced cell death. Our data reveal a novel role for CaeB in ER stress signalling modulation and demonstrate that CaeB is involved in pathogenicity in vivo. Furthermore, we provide evidence that C. burnetii infection leads to modulation of the ER stress sensors IRE1 and PERK, but not ATF6 during ER stress. While the upregulation of the RNase activity of IRE1 during ER stress depends on CaeB, modulation of PERK is CaeB independent, suggesting that C. burnetii encodes several factors influencing ER stress during infection.
CRIS-Team WoS Importer:2021-02-12